2014
DOI: 10.1371/journal.pone.0104606
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell-Mediated, DNA-Based Vaccination against Hepatitis C Induces the Multi-Epitope-Specific Response of Humanized, HLA Transgenic Mice

Abstract: Hepatitis C virus (HCV) is the etiologic agent of chronic liver disease, hepatitis C. Spontaneous resolution of viral infection is associated with vigorous HLA class I- and class II-restricted T cell responses to multiple viral epitopes. Unfortunately, only 20% of patients clear infection spontaneously, most develop chronic disease and require therapy. The response to chemotherapy varies, however; therapeutic vaccination offers an additional treatment strategy. To date, therapeutic vaccines have demonstrated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…99 A recent experimental study in mice also showed that multi-epitopebased HCV vaccine targeting DCs offers an effective approach to inducing a broad immune response and viral clearance in chronic, HCV-infected patients. 100 As for this type of vaccines, no active human clinical trial has been reported. 86…”
Section: Dendritic Cell-based Vaccination Strategiesmentioning
confidence: 99%
“…99 A recent experimental study in mice also showed that multi-epitopebased HCV vaccine targeting DCs offers an effective approach to inducing a broad immune response and viral clearance in chronic, HCV-infected patients. 100 As for this type of vaccines, no active human clinical trial has been reported. 86…”
Section: Dendritic Cell-based Vaccination Strategiesmentioning
confidence: 99%
“…Dendritic cell‐based vaccines are now being developed by transfecting dendritic cells with plasmids encoding HCV antigens. In 2014, a dendritic cell‐based vaccine study in mice has demonstrated an effective immune response and viral clearance . However, no human clinical trial is being conducted using dendritic cell‐based vaccine.…”
Section: Strategies For Pangenotypic Therapiesmentioning
confidence: 99%
“…Significant advancements in immunome-derived, epitopedriven vaccines designed using the iVAX toolkit have been made in recent years; in particular, basic research studies have demonstrated the ability of the tools to select epitopes for Burkholderia species, 29 H. pylori 30 and HCV, [31][32][33] and validated the importance of the presence of T cell epitopes in subunit vaccines. Recently, the collaborating groups at EpiVax and iCubed discovered epitopes that activate T regulatory cells (Tregs) in viral pathogens using the JanusMatrix tool.…”
Section: Computational Vaccinologymentioning
confidence: 99%